2020
DOI: 10.1371/journal.pone.0231447
|View full text |Cite
|
Sign up to set email alerts
|

Role of intraoperative oliguria in risk stratification for postoperative acute kidney injury in patients undergoing colorectal surgery with an enhanced recovery protocol: A propensity score matching analysis

Abstract: Background The enhanced recovery after surgery (ERAS) protocol for colorectal cancer resection recommends balanced perioperative fluid therapy. According to recent guidelines, zero-balance fluid therapy is recommended in low-risk patients, and immediate correction of low urine output during surgery is discouraged. However, several reports have indicated an association of intraoperative oliguria with postoperative acute kidney injury (AKI). We investigated the impact of intraoperative oliguria in the colorectal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
(50 reference statements)
1
11
0
Order By: Relevance
“…In this study, duration of bypass was identified as one of the predictors of postoperative AKI with an odds ratio of 1.01 and p value = .004. Karim HMR et al 19 found in their study that a bypass duration more than 70 min increased the risk of AKI associated with cardiac surgery with an odds ratio of 4.76 (p value <.05).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In this study, duration of bypass was identified as one of the predictors of postoperative AKI with an odds ratio of 1.01 and p value = .004. Karim HMR et al 19 found in their study that a bypass duration more than 70 min increased the risk of AKI associated with cardiac surgery with an odds ratio of 4.76 (p value <.05).…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, oliguria was not observed in any of the patients, possibly due to the routine mannitol infusion during bypass as well as the maintenance of adequate systemic blood pressure and subsequently renal blood flow due to relatively low regional vascular resistance during CPB. 19 Similar to our study, Habib et al, 19 in a study of cardiac surgery patients found that the intraoperative U/ O was not significantly different between the two groups of AKI and non-AKI and concluded that U/O is not a reliable indicator of CSA-AKI In contrast, Hori et al in a prospective study of 579 cardiac surgery patients found that patients with AKI had lower urine flow rate than those without AKI (p < .001)and reported that there was an independent correlation between low U/O of less than 1.5 mL/kg/h and postoperative AKI. 10 Young Song et al 11 also retrospectively studied 696 patients who underwent cardiovascular surgery with CPB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerns have arisen regarding restrictive fluid regimens and the risk of acute kidney injury (AKI) especially with concurrent administration of nephrotoxic agents [ 44 ]. Postoperative AKI is associated with poor clinical outcomes [ 45 ], and it is suggested that intraoperative oliguria may be used to screen for AKI [ 46 ], along with the presence of pre-existing chronic kidney disease [ 44 ] and low albumin levels [ 45 ]. The RELIEF study compared patients receiving a liberal versus restrictive fluid therapy [ 47 ], with the latter associated with a significantly higher AKI incidence, renal replacement therapy and surgical site infection.…”
Section: Components Of Erpsmentioning
confidence: 99%
“…Studies report a prevalence of 3%–35% for postoperative AKI and 0.5%–25% for all-cause postoperative mortality within the first year in patients who have undergone major abdominal surgery[ 86 ]. Postoperative AKI occurred in 17.4%–20.3% of patients who underwent laparoscopic CRC resection[ 27 , 87 ]. Of 4718 patients who underwent gastric cancer surgery, 14.4% developed postoperative AKI[ 13 ].…”
Section: Surgery-related Akimentioning
confidence: 99%